Sistem Pengadaan dan Distribusi Sarana Produksi Melon Inthanon di Pesantren Al-Kautsar 561 - Dudung Dudung; Apdan Pebriana; Rina Nuryati; Candra Nuraini (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2024)
Al-kautsar 561 Islamic Boarding School Agriculture in carrying out the program to provide agricultural production facilities has problems in the procurement and distribution process of agricultural production facilities. The purpose of this paper is: (1) To examine the saprotan supply program and the saprotan procurement planning system in agriculture at Al-kautsar 561 Islamic Boarding School, (2) To study the saprotan procurement system in agriculture at Al-kautsar 561 Islamic Boarding School, and (3) To study the saprotan distribution system in Al-kautsar 561 Islamic Boarding School. The data collection method used is the method of active participation, observation, and active role in agricultural activities at the Al-kautsar 561 Islamic Boarding School. Using primary data and secondary data and using qualitative descriptive analysis. The process of procurement of agricultural production facilities uses a centralized system, namely by the Supply Chain Officer, the process of distributing agricultural production facilities uses a direct distribution system.